Digitalisasi UMKM Berbasis E-Commerce: Pelatihan, Pendampingan, dan Implementasi UMKM Go Digital: Pengabdian - Dessyana Suryawandari; Aghil Satrio Wicaksono; Made Wulan Febryani; Risma Dila Agustin; Wahyu Ragil Pamungkas5; Erna Fitri Komariyah; Akhmad Afnan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to assist micro, small, and medium enterprises (MSMEs) in the digitalization process by utilizing Shopee as an e-commerce platform. The partner MSME involved is Sugar Craft Hampers, a woven bag handicraft business located in Sleman, Yogyakarta. This initiative is driven by the need for MSMEs to enhance competitiveness and expand market reach through the use of digital technology. The methods employed include identifying the problems faced by the MSME, conducting training on Shopee features, creating and optimizing digital content (product displays, photos, descriptions, and pricing), implementing digital marketing strategies, and evaluating sales outcomes. The results indicate a significant improvement in the digital literacy of MSME owners, a broader market reach, and increased online sales. This assistance demonstrates that digitalization through e-commerce can serve as a strategic and practical solution for enhancing the sustainability of micro-enterprises in the digital economy era. Furthermore, this activity underscores the crucial role of higher education institutions in bridging the technology gap between MSMEs and the rapidly evolving digital landscape.